Debatable issues in describing criminal law, its subject, and ways of criminal law regulation - I.A. Tarkhanov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article discusses the results of an analysis of the extensive doctrinal and normative material on the essence of criminal law, its subject, and the ways of criminal law regulation. The argumentation is built up as several thematic blocks that allow one to approach the problem under consideration from different angles. Various aspects of the phenomenon of criminal law were studied. It was revealed that criminal law plays a regulatory role in certain spheres of social life and that the term “criminal law” has no clear definition, i.e., different meanings are attributed to criminal law in the legal sources under study, which should be taken into account while trying to understand its nature and features. It was concluded that the state (as a legislator) has a direct criminal law influence on such relations that arise in connection with the criminal law prohibition and that there are some differences between the concepts of “criminal law influence” and “criminal law regulation”. The concept of “criminal law influence” is broader and includes all forms of the impact of law on the normal functioning of the relations protected and ensured by means of criminal law.